Captura de carbono como criterio para la conservación de la caoba (Swietenia macrophylla King) en el campus politécnico de la ESPAM-MFL - Ganchozo Dávila, Gema Tatiana (2022)
The objective of this research was to estimate carbon sequestration as a criterion for the conservation of mahogany (Swietenia macrophylla) in the following areas: agroindustrial, forest and the City of Agricultural Research, Innovation and Development [CIIDEA] of the Polytechnic Campus at ESPAM MFL. A non-experimental quantitative research was carried out, using a total sampling to quantify the mahogany individuals present, obtaining in the agroindustrial area 161, forest 257 and CIIDEA 1.239, with a total of 1.657 for the calculation of carbon sequestration, with the basic information obtained from the diameter and height of each one of them, an allometric model was applied that takes into account the estimation of basal area, volume, forest biomass, carbon estimation and carbon stored of this species. It was determined that the total value of carbon stored in the agroindustrial area was 6,47 t/CO2, forest 3205,37 t/CO2 and in CIIDEA 1534,01 t/CO2, which reflects that the forest is the study area that captures more carbon, due to the large diameter and height of the mahogany individuals in the study area. Conservation strategies were proposed to improve knowledge regarding its conservation, use and proper management. It is concluded that the mahogany plantations on the polytechnic campus reflect large amounts of captured carbon.